Developing an E-book with Past Tenses Materials for the Students of English Education Study Program in the Indonesian Context - Nurul Fitriyah Almunawaroh; Kuntum Trilestari; Ayu Riani (UIR Press, 2021)
An e-book is one type of instructional materials that play important roles to ensure learning interactivity by integrating technology to its context. However, studies on the integration of an e-book in English language teaching mostly focus on its implementation process, not its developing process which in fact may influence the validity quality of an e-book. Thus, this study aims to use expert’s review to develop an e-book with past tenses materials for students of English study program. Development research design proposed by Akker was used to develop the e-book. Expert’s reviews on the past tenses materials and the e-book media design were used to determine the validity of the e-book. The results showed that the e-book with past tenses materials was valid which indicated that it can be employed in teaching and learning simple past tense and past continuous to the students of English education study program.